NAROS: Northern Areas Open Scholarly Documents - Longva, Leif (Nordlit, 2008)
A living discourse needs to be communicated and disseminated. The Internet is a very powerful tool in this respect. Internet has been around for a while now, but how to utilize the Internet as a communication and dissemination tool, is still evolving (Tananbaum, 2007). NAROS is a planned service. The intention of NAROS is to utilize the possibilities of the Internet to improve the awareness and the accessibility of scholarly works on topics related to northern areas, thus hopefully paving the way for expanding the arctic discourses. NAROS will collect information on applicable documents through a standard way of automatically harvesting metadata, and utilize the fast growing trend of making scholarly works available through open archives and open access journals. Through the search service of NAROS, researchers, students, and others will have easy access to scholarly documents within the thematic scope of the northern areas.